Restoration of a molar tooth using hybrid ceramic overlay - Gábor András Suta; Csaba Hegedűs (Hungarian Dental Association, 2024)
Thanks to developments in dental CAD/CAM technology, a variety of materials are now available for dental restorations, including different types of hybrid ceramics, also known as resin matrix ceramics. Hybrid ceramics are characterized by their inorganic ceramic content and varying proportions of organic polymer content. Additionally, the structure and composition of the ceramic grains differ across products. Hybrid ceramics are primarily utilized for individual restorations, such as crowns, veneers and inlays/onlays/overlays. This case study presents the use of Vita Enamic (Vita Zahnfabrik, Germany) hybrid ceramic overlay for restoring a lower root canal treated molar tooth. Overall, hybrid ceramics are considered suitable for the mechanical and aesthetic restoration of teeth.